Bioimaging application of pyrene-graphene quantum dot - Ban, Lai Theng (2017)
GQDs, a nanometer-sized fragment of graphene, are a relatively recent nanomaterial. As they are expected to outperform the current fluorescent probes in several applications, a deluge of attention has been aroused and considerable research interest has been attracted over the past decades. Recently, efforts on the synthesis through either bottom-up or top-down approaches of multifunctional GQDs have been made by researchers around the globe, among which, using low toxicity and inexpensive pyrene (C₁₆H₁₀) as the carbon precursor by hydrothermal treatment in different alkaline aqueous solutions has been reported recently by Wang et al. This is because pyrene-derived GQDs (P-GQDs) have been revealed that having excellent optical properties in terms of highly excitonic fluorescence band, large molar attenuation coefficients, high quantum yield and long-term photostability, making them the favored subject for various chemical and biological applications. In this effort, P-GQDs was fabricated by using pyrene as precursors and sodium bicarbonate (NaHCO₃) solution as hydrothermal media to investigate their structural characteristics and optical properties, followed by introducing an overview on their application for in vitro fluorescence imaging in HeLa and HepG2 cells. Finally, the application of P-GQDs in bioimaging would be proved owing to their excellent photoluminescence (PL) properties, low cytotoxicity and so on.